Analisis Akuntansi Atas Biaya Lingkungan Dalam Proses Pengelolaan Limbah Medis Puskesmas Kecamatan Cakung Kota Jakarta Timur - Intan Ariza Farhanah; Hera Khairunnisa; Dwi Handarini (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the application of environmental cost accounting in the medical waste management process at the Cakung District Public Health Center, East Jakarta. The research focuses on identifying environmental activities, the types of environmental costs incurred, as well as the accounting treatment of environmental costs, which includes the stages of identification, recognition, measurement, presentation, and disclosure in the health center’s financial statements. This study employs a qualitative approach using a case study method. The data sources consist of primary and secondary data obtained through interviews, observations, and documentation. The findings indicate that the public health center has not yet specifically classified environmental costs, resulting in medical waste management costs being recorded under general operational expenses. This condition leads to the absence of separate environmental cost information and limits transparency and accountability in financial reporting. The results show that the health center has implemented medical waste management activities in accordance with applicable regulations, including waste segregation, containment, temporary storage, sterilization, and transportation and disposal through licensed third parties. However, the associated costs have not been classified based on environmental cost components. Therefore, this study recommends the systematic classification and disclosure of environmental costs to enhance the quality of transparent and accountable financial reporting at public health centers.